Electric connection member material and electric connection member

JP2025031768AActive Publication Date: 2025-03-07AUTONETWORKS TECH LTD +2
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024221368
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-07
Estimated Expiration
2041-03-24

AI Technical Summary

Benefits of technology

【0008】 本開示にかかる電気接続部材用材料および電気接続部材は、特殊な金属層を用いなくても、Ag層における凝着を抑制することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025031768000001_ABST
    Figure 2025031768000001_ABST
Patent Text Reader

Abstract

To provide an electric connection member material capable of suppressing adhesion in an Ag layer even without using a special metal layer, and an electric connection member.SOLUTION: An electric connection member material 1 includes: a metal material 10 having an Ag layer 13 on the surface; and a coating layer 2 for coating the surface of the metal material 10. The coating layer 2 is formed to contact an organic compound having a mercapto group and an aromatic ring to the surface of the metal material 10, where a case that the surface of the Ag layer 13 has a hardness of 90 HV or more is excluded. An electric connection member includes the electric connection member material 1.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a material for an electrical connection member and an electrical connection member. [Background technology]

[0002] In electrical connection components such as connector terminals for high currents used in automobiles, metal materials with an Ag layer formed on the surface by plating or the like are sometimes used. Metal materials with an Ag layer have excellent heat resistance, corrosion resistance, and electrical conductivity, but due to the soft nature of Ag, which is prone to adhesion, they are prone to surface wear and peeling. If part of the Ag layer is removed by wear or peeling, exposing the underlying metal such as the base material or undercoat layer, the electrical connection properties of the surface will change. Wear and peeling of the Ag layer due to adhesion is particularly likely to occur in high-temperature environments.

[0003] In order to suppress adhesion on the surface of the Ag layer, materials constituting the metal material have been studied. As one direction of material study, it has been considered to provide a predetermined Ag alloy layer on the surface of the metal material instead of the Ag layer, or to provide a base layer made of a predetermined metal under the Ag layer or Ag alloy layer. Studies in this direction are disclosed, for example, in Patent Document 1. In another direction, an attempt has been made to suppress adhesion of the Ag layer by providing a metal layer having a predetermined composition on the surface of a counterpart member that is to be in contact with an electrical connection member having an exposed Ag layer on its outermost surface. Studies in this direction are disclosed, for example, in Patent Document 2. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-196911 A [Patent Document 2] JP 2017-162598 A Summary of the Invention [Problem to be solved by the invention]

[0005] In metal materials containing Ag in the surface layer, as described in Patent Documents 1 and 2, it is an effective means to reduce adhesion of Ag by devising the composition or structure of the surface layer or the other metal layer in contact with the surface layer. However, if it is possible to suppress wear and peeling caused by Ag adhesion in a general metal material having an Ag layer without using a metal layer having a special composition or structure, and further suppress these phenomena in a high-temperature environment, the metal material having an Ag layer can be more easily used as an electrical connection member such as a terminal. Therefore, the objective of the present invention is to provide a material for electrical connection members and an electrical connection member that can suppress adhesion in the Ag layer without using a special metal layer. [Means for solving the problem]

[0006] The material for electrical connection members disclosed herein comprises a metal material having a Ag layer on its surface, the Ag layer having a surface hardness of 90 HV or more, and a coating layer that coats the surface of the metal material, and the coating layer is formed by contacting the surface of the metal material with an organic compound having a mercapto group.

[0007] The electrical connection member of the present disclosure is configured to contain the material for an electrical connection member. Effect of the Invention

[0008] The material for an electrical connection member and the electrical connection member according to the present disclosure can suppress adhesion in the Ag layer without using a special metal layer. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram showing a cross section of a material for an electrical connection member according to one embodiment of the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view showing a connection terminal as an electrical connection member according to one embodiment of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] [Description of the embodiments of the present disclosure] First, embodiments of the present disclosure will be listed and described.

[0011] The material for electrical connection members according to the present disclosure comprises a metal material having a Ag layer on its surface, the Ag layer having a surface hardness of 90 HV or more, and a coating layer that coats the surface of the metal material, and the coating layer is formed by contacting the surface of the metal material with an organic compound having a mercapto group.

[0012] When the electrical connection member material comes into contact with another member on its surface, the Ag layer having a surface hardness of 90HV or more comes into contact with the other member through the coating layer. The Ag layer is configured as a hard Ag layer having a hardness of 90HV or more, and the surface of the hard Ag layer is coated with a coating layer formed using an organic compound having a mercapto group, so that when the electrical connection member material comes into contact with or slides against another member, adhesion of Ag and the associated wear and peeling of the Ag layer are unlikely to occur. The coating layer formed from an organic compound having a mercapto group stably maintains the state in which the surface of the Ag layer is coated even at high temperatures, and is highly effective in suppressing adhesion of the Ag layer even in a high-temperature environment.

[0013] Here, it is preferable that the organic compound has an aromatic ring, so that the state in which the surface of the Ag layer is covered with the coating layer can be stably maintained even at high temperatures, and the effect of suppressing adhesion of the Ag layer in a high-temperature environment can be highly obtained.

[0014] In this case, the aromatic ring is preferably a heterocycle containing at least one of an S atom and an N atom in addition to a C atom. This further increases the stability of the state in which the surface of the Ag layer is covered with the coating layer, and can highly suppress adhesion of the Ag layer even when exposed to a high temperature environment or when a large surface pressure is applied to the surface of the material for electrical connection members.

[0015] The electrical connection member according to the present disclosure is configured to include the material for electrical connection members. As described above, the surface of the material for electrical connection members according to the present disclosure is a hard Ag layer covered with a coating layer formed using an organic compound having a mercapto group, so that even if it comes into contact or slides with other members, it is unlikely to wear or peel off due to adhesion. In addition, even in a high-temperature environment, these phenomena caused by Ag adhesion can be suppressed. By forming an electrical connection member using a material having such characteristics, it becomes an electrical connection member that is unlikely to wear or peel off the Ag layer due to adhesion, and can further suppress the occurrence of these phenomena even in a high-temperature environment.

[0016] Here, the electrical connection member is preferably configured as a connection terminal having a contact portion that electrically contacts with a counterpart conductive member, and the coating layer is preferably formed on the surface of the metal material at least in the contact portion. In this way, adhesion of the Ag layer due to contact or sliding with the counterpart conductive member and the associated wear and peeling of the Ag layer are unlikely to occur in the contact portion of the connection terminal, and the electrical connection characteristics, heat resistance, and other characteristics imparted to the contact portion by the Ag layer can be well maintained. Furthermore, even when the contact portion is heated due to current flow or the like, adhesion is unlikely to occur on the surface of the Ag layer, and the characteristics imparted by the Ag layer can be maintained.

[0017] In this case, the surface pressure applied to the contact portion is preferably 30 MPa or more. In a connection terminal, the greater the surface pressure applied to the contact portion, the more likely adhesion occurs in the metal layer on the surface of the contact portion, but in the above-mentioned electrical connection member, a hard Ag layer is formed on the surface of the contact portion and the surface of the hard Ag layer is covered with a coating layer, so that adhesion of Ag and the resulting wear and peeling of the Ag layer are less likely to occur on the surface of the contact portion.

[0018] [Details of the embodiment of the present disclosure] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the drawings.

[0019] <Outline of materials for electrical connection members and electrical connection members> First, the configuration of the material for electrical connection members and the electrical connection member according to the embodiments of the present disclosure will be briefly described.

[0020] (Electrical connection materials) The material for electrical connection according to the embodiment of the present disclosure has a structure in which the surface of a metal material is covered with a coating layer. The material for electrical connection according to the embodiment of the present disclosure can be suitably used as a material for forming an electrical connection member such as a connection terminal.

[0021] 1 shows a cross-sectional view of a configuration of a material for electrical connection members (hereinafter, may be referred to as a connecting material) 1 according to a first embodiment of the present disclosure. The connecting material 1 has a metal material 10 and a coating layer 2 that coats the surface of the metal material 10. The metal material 10 has a base material 11 and an Ag layer 13. In addition, an underlayer 12 is optionally provided between the base material 11 and the Ag layer 13.

[0022] The substrate 11 of the metal material 10 is configured as a metal plate. The specific metal species constituting the substrate 11 is not particularly limited, but Cu or a Cu alloy, which is widely used as a substrate for electrical connection members such as connection terminals, can be preferably used because of its excellent electrical conductivity and mechanical properties.

[0023] The Ag layer 13 is formed as a layer of hard Ag and is exposed on the outermost surface of the metal material 10. The hard Ag has a surface hardness of about 90HV or more, preferably 110HV or more. The Ag layer 13 may contain only Ag and unavoidable impurities, or may contain an additive element for hardening the Ag layer 13 in addition to Ag and unavoidable impurities. Examples of such additive elements include Se, Sb, C, N, and S. In particular, Se, C, and S are preferably used as additive elements. The amount of the additive element added may be in the range of 0.1 atomic % or more and 5.0 atomic % or less relative to Ag atoms. The hardness measurement in this specification indicates a value obtained when a measurement is performed at HV0.01 (10gf) in a micro Vickers hardness test according to JIS Z 2244:2009.

[0024] The thickness of the Ag layer 13 is not particularly limited, but is preferably 1 μm or more, more preferably 3 μm or more, from the viewpoint of fully exerting the properties of Ag. On the other hand, from the viewpoint of avoiding the use of an excessive amount of Ag, it is preferably 100 μm or less. The Ag layer 13 may be formed by any method such as a plating method or a vapor deposition method. The use of a plating method is particularly preferable from the viewpoint of simplicity, hardness control, etc.

[0025] Another metal layer may be provided between the substrate 11 and the Ag layer 13 as the underlayer 12, if necessary. The underlayer 12 may be a single layer, or may be a laminate of two or more metal layers. When the substrate 11 is made of Cu or a Cu alloy, a suitable example of the underlayer 12 is a layer made of Ni or a Ni alloy. The underlayer 12 made of Ni or a Ni alloy suppresses the diffusion of Cu atoms from the substrate 11 to the Ag layer 13, and plays a role in increasing the adhesion of the Ag layer 13 to the substrate 11. In the metal material 10, at the interface between adjacent layers, some of the metal atoms constituting the layers on both sides may form an alloy.

[0026] The connecting material 1 according to this embodiment is provided with a coating layer 2, which is in contact with the surface of the Ag layer 13 exposed on the surface of the metal material 10 and covers the Ag layer 13. The coating layer 2 is a layer formed by bringing an organic compound having a mercapto group (-SH group) into contact with the surface of the Ag layer 13 of the metal material 10. The details of the coating layer 2 will be described in detail later, but since the coating layer 2 covers the surface of the Ag layer 13, it exhibits the effect of suppressing adhesion of Ag and the accompanying wear and peeling of the Ag layer 13. In addition, even when the metal material 10 is heated to a high temperature, wear and peeling of the Ag layer 13 due to adhesion are suppressed.

[0027] (Electrical connection parts) Next, an electrical connection member according to an embodiment of the present disclosure will be described. The electrical connection member according to this embodiment is configured to include the material for electrical connection member 1 according to an embodiment of the present disclosure described above.

[0028] An example of an electrical connection member is a connection terminal. The connection terminal has a contact portion that electrically contacts with a counterpart conductive member, and at least in the contact portion, the surface of the substrate 11 has an Ag layer 13 made of hard Ag and a coating layer 2 that covers the surface of the Ag layer 13. As long as the Ag layer 13 and the coating layer 2 are formed at least in the contact portion on the surface of the connection terminal, the Ag layer 13 and the coating layer 2 may cover the entire surface of the connection terminal or only a partial area.

[0029] The specific type and shape of the connection terminal are not particularly limited. FIG. 2 shows a female connector terminal 20 as an example of a connection terminal according to an embodiment of the present disclosure. The female connector terminal 20 has the same shape as a known mating type female connector terminal. That is, a clamping portion 23 is formed in a cylindrical shape with an opening at the front, and a resilient contact piece 21 is formed on the inside of the bottom surface of the clamping portion 23, the resilient contact piece 21 being folded back toward the inside rear side as a mating conductive member. When a flat tab-shaped male connector terminal 30 is inserted into the clamping portion 23 of the female connector terminal 20 as a mating conductive member, the resilient contact piece 21 of the female connector terminal 20 comes into contact with the male connector terminal 30 at the embossed portion 21a bulging toward the inside of the clamping portion 23, and applies an upward force to the male connector terminal 30. The surface of the ceiling of the clamping portion 23 facing the elastic contact piece 21 is made into the internal facing contact surface 22, and the male connector terminal 30 is pressed against the internal facing contact surface 22 by the elastic contact piece 21, thereby clamping and holding the male connector terminal 30 within the clamping portion 23.

[0030] The female connector terminal 20 is entirely made of the metal material 10 having the Ag layer 13 on the outermost surface as described above. Here, the surface of the metal material 10 on which the Ag layer 13 is formed faces the inside of the clamping portion 23, and is disposed so as to form the mutually opposing surfaces of the elastic contact piece 21 and the inner facing contact surface 22. A coating layer 2 is formed on the surface of the metal material 10 in a region including the embossed portion 21a of the elastic contact piece 21 and the inner facing contact surface 22.

[0031] At the surface of the embossed portion 21a and the inner facing contact surface 22 that contact the surface of the male connector terminal 30, the surface of the Ag layer 13 is covered with the coating layer 2, and the coating layer 2 exerts an adhesion suppressing effect on the Ag layer 13 at these locations. As a result, even if sliding occurs when inserting the male connector terminal 30 into the clamping portion 23 of the female connector terminal 20, the Ag layer 13 is unlikely to wear or peel off due to adhesion. Furthermore, even if the male connector terminal 30 and the female connector terminal 20 are left in a mated state for a long period of time, or even if they are heated to a high temperature by current flow while in the mated state, the Ag layer 13 is unlikely to wear or peel off due to Ag adhesion. In the female connector terminal 20, the surface pressure of the contact portion, that is, the surface pressure applied from the top of the embossed portion 21a to the surface of the male connector terminal 30 by the elastic restoring force of the elastic contact piece 21 is preferably 30 MPa or more, and further preferably 40 MPa or more. The greater the surface pressure, the stronger the force with which the Ag layer 13 on the surface is pressed against the surface of the male connector terminal 30 at the top of the embossed portion 21a, making it easier for the Ag layer 13 to adhere to the surface, but since the surface of the Ag layer 13 is covered with the covering layer 2, adhesion of Ag can be effectively suppressed even in a situation where a large surface pressure is applied as described above. However, when a surface pressure of about 4 to 5 times the hardness of the Ag layer 13 on the surface is applied, the deformation of the Ag layer 13 at the point in contact with the surface of the male connector terminal 30 changes from elastic deformation to plastic deformation, so it is preferable to keep the surface pressure at 5 times the hardness of the Ag layer 13 or less.

[0032] Here, the female connector terminal 20 is entirely made of a metal material 10 having an Ag layer 13, and only the portion of the Ag layer 13 that contacts the male connector terminal 30 is covered with the coating layer 2. However, as described above, as long as the Ag layer 13 and the coating layer 2 are formed at least on the surface of the contact portion that contacts the mating conductive member, the range in which each of these layers is formed is not particularly limited. In addition, the material of the male connector terminal 30 is not particularly limited, but it is preferable that the male connector terminal 30 is also made of the connecting material 1 according to the embodiment of the present disclosure, in which at least the contact portion, that is, the surface of the tab-shaped portion that contacts the female connector terminal 20, has the Ag layer 13 formed as a layer of hard Ag on the surface of the substrate 11, like the female connector terminal 20, and the surface of the Ag layer 13 is further covered with the coating layer 2. In this case, in the electrical connection between the female connector terminal 20 and the male connector terminal 30, the Ag layers 13 made of hard Ag come into contact with each other through the two coating layers 2. This makes it possible to effectively suppress wear and peeling of the Ag layer 13 due to adhesion not only at the contact points of the female connector terminal 20 but also at the contact points of the male connector terminal 30, and these effects are sustained even over long periods of time or in high-temperature environments.

[0033] The connection terminal according to the embodiment of the present disclosure can be in various forms, such as the mating type female connector terminal 20 or male connector terminal 30 as described above, as well as a press-fit terminal that is press-fitted into a through hole formed in a printed circuit board. The various connection terminals according to the embodiment of the present disclosure can be used in the form of a connector, for example, by being housed in a connector housing made of an insulating material. Also, the connector can be connected to the end of an electric wire to be used in the form of a wire harness.

[0034] <Coating layer composition and adhesion suppression effect> As described above, in the connecting material 1 according to the embodiment of the present disclosure, the Ag layer 13 made of hard Ag is formed on the surface of the metal material 10, and the surface of the Ag layer 13 is covered with the coating layer 2 formed of an organic compound having a mercapto group (-SH group). Ag is a metal that is prone to adhesion, but by being covered with the coating layer 2, the occurrence of adhesion in the Ag layer 13 is suppressed.

[0035] Here, a brief description will be given of the situation in which the Ag layer is exposed on the outermost surface of the connecting material without being covered by other layers. Ag is a metal that is relatively resistant to oxidation, and exhibits low contact resistance on the surface, and is also excellent in heat resistance and corrosion resistance. By providing an Ag layer on the surface of a connecting material that is used as a material for a connecting terminal, etc., it is easy to maintain good electrical properties even in a high-temperature environment. On the other hand, Ag has a property that it is very susceptible to adhesion, and if adhesion occurs at the contact part with the counter member, the Ag on the surface will wear or peel off when the contact part is slid or left in contact with the counter member. In a connecting material having an Ag layer on its surface, if Ag wears or peels off due to adhesion, the properties of Ag, such as low contact resistance and heat resistance, cannot be fully utilized in the connecting material. Furthermore, if the base material, such as Cu or Cu alloy, present under Ag, or the underlayer, such as Ni or Ni alloy, is exposed due to the wear or peeling of Ag, the properties of the connecting material, such as electrical connection properties, may be significantly affected. In particular, when an Ag layer is formed on the surface of the counter member, the Ag layers come into contact with each other on their surfaces, and adhesion and the associated wear and peeling are likely to occur in both Ag layers. Furthermore, when the Ag layer on the surface is placed in a high-temperature environment while in contact with the counter member, or when a large contact load (surface pressure) is applied, adhesion is more likely to progress due to creep and atomic diffusion.

[0036] However, in the connecting material 1 according to the embodiment of the present disclosure, the Ag layer 13 on the surface of the metal material 10 is covered with the coating layer 2. When the connecting material 1 comes into contact with another member, the Ag layer 13 does not come into direct contact with the surface of the counter member, but the coating layer 2 is interposed between the Ag layer 13 and the counter member, so that the Ag layer 13 is less likely to adhere due to contact or sliding with the counter member. As a result, wear or peeling of the Ag layer 13 caused by adhesion of Ag is less likely to occur, and the properties of the Ag layer 13, such as low contact resistance and heat resistance, are easily maintained even after contact or sliding with the counter member. In particular, in this embodiment, the coating layer 2 is formed by contacting an organic compound having a mercapto group with the Ag layer 13, so that the state in which the coating layer 2 covers the surface of the Ag layer 13 is stably maintained. This is considered to be due to the fact that Ag atoms and S atoms easily form bonds, etc., and the coating layer 2 is firmly fixed to the surface of the Ag layer 13. Furthermore, the state in which the coating layer 2 covers the surface of the Ag layer 13 is stably maintained even at high temperatures. Therefore, even if the connecting material 1 is placed in a high-temperature environment, the Ag layer 13 is unlikely to come into direct contact with the surface of the counter member, and adhesion of the Ag layer 13 and the resulting wear and peeling are unlikely to occur. In addition, even when a high load is applied to the contact portion with the counter member, the presence of the coating layer 2 suppresses adhesion of the Ag layer 13.

[0037] For these reasons, the connecting material 1 according to the present embodiment can be suitably used as a constituent material of a connecting terminal that is easily heated by heating from the surrounding environment or heat generated by current flow. An example of such a connecting terminal is a connecting terminal for an automobile. In addition, in the connecting material 1 according to the present embodiment, a high adhesion suppression effect can be obtained by simply contacting a predetermined organic compound with the surface of the Ag layer 13 configured as a hard Ag layer to form the coating layer 2, and since a special metal layer is not required for adhesion suppression, it has high versatility. A high adhesion suppression effect can be imparted to a connecting material having a conventional or existing hard Ag layer by simply forming the coating layer 2.

[0038] In the connecting material 1 according to the present embodiment, the Ag layer 13 provided on the surface of the metal material 10 is formed as a hard Ag layer. By making the Ag layer 13 out of hard Ag, the adhesion of Ag can be highly suppressed on the surface where the Ag layer 13 is covered with the coating layer 2, compared to the case where the Ag layer 13 is made of soft Ag, the surface hardness of which is generally 60 HV or less. One of the factors of the high adhesion suppression effect is the high hardness of the hard Ag layer itself. Although Ag is a metal that easily causes adhesion, adhesion can be suppressed to a certain extent by increasing the surface hardness by adding a small amount of additive elements or controlling crystal growth. Furthermore, as another factor, as shown in the later examples, by covering the surface of Ag with the coating layer 2 formed from an organic compound having a mercapto group, the magnitude of the adhesion suppression effect, that is, the degree of adhesion reduction based on the case where the coating layer 2 is not formed, is larger in the case of the hard Ag layer than in the case of the soft Ag layer. This is presumably because, in the case of a soft Ag layer, the Ag layer deforms due to plastic deformation and the coating layer cannot follow the deformation, resulting in gaps in the coating layer, causing adhesion to proceed through these gaps. In contrast, in the case of a hard Ag layer, plastic deformation is less likely to occur and defects are less likely to occur in the coating layer 2, so that the Ag layer 13 is less likely to come into direct contact with the surface of the opposing conductive member.

[0039] In this embodiment, the coating layer 2 is formed by contacting an organic compound having a mercapto group with the Ag layer 13, but the organic compound does not need to maintain its original state in the formed coating layer 2. For example, the organic compound may constitute the coating layer 2 in a thiolate state in which the SH bond of the mercapto group (-SH group) is cleaved and the H atom is removed. In this case, the organic compound used to form the coating layer 2 is expressed as R-SH, and an S-Ag bond is formed between the organic compound and the Ag layer 13, and the organic compound may be firmly bound to the Ag layer 13 in the form of an RS-Ag structure. The formation of this structure is particularly preferable from the viewpoint of increasing the stability of the coating layer 2. Alternatively, it is also possible that the bond between the C atom constituting the organic compound and the mercapto group (-SH group) is cleaved, and the organic compound is bound to the Ag layer 13 in the form of R-Ag.

[0040] In addition, a form in which an organic compound containing a mercapto group (-SH group) is converted into a form having a sulfur-containing functional group other than a mercapto group to form the coating layer 2 is also conceivable. Examples of sulfur-containing functional groups other than a mercapto group include a sulfide bond (-S-), a disulfide bond (-SS-), a thiocyanate group (-SC=N), an isothiocyanate group (-N=C=S), a sulfo group (-SO3), a sulfonyl group (-SO2-), a sulfinyl group (-S(=O)-), a thioester group (-SC(=O)-), a thiocarbonyl group (>C=S), and a thiocarboxyl group (-C(=O)-SH). In addition, in the R-SH structure of an organic compound having a mercapto group, the R portion may be cleaved or converted. When the R portion includes a ring structure, an example of the cleavage of the bond may be the opening of the ring structure. In these cases, when an organic compound containing a mercapto group is converted into another form to form the coating layer 2, the coating layer 2 does not necessarily have to be formed by contacting an organic compound containing a mercapto group with the Ag layer 13. For example, the compound itself having the converted form may be contacted with the surface of the Ag layer 13 to form the coating layer 2. Regardless of the manufacturing method, as long as the organic compound forming the coating layer 2 on the surface of the Ag layer 13 has the same form, the coating layers 2 show the same effect of suppressing adhesion to the Ag layer 13. The organic compound constituting the coating layer 2 may be in a substantially single state or may be in a mixture of two or more states, for example, a state in which the SH bond is cleaved and a state in which the SH bond is not cleaved.

[0041] The thickness of the coating layer 2 is not particularly limited. For example, the thickness may be 1 nm or more from the viewpoint of enhancing the effect of suppressing adhesion of the Ag layer 13 by the coating layer 2. On the other hand, the thickness may be 10 μm or less from the viewpoint of preventing the outflow of excess organic compounds and stickiness.

[0042] When the organic compound having a mercapto group is brought into contact with the Ag layer 13 to form the coating layer 2, the specific form of contact is not particularly limited, and examples of contact methods include coating, immersion, dropping, flow, and spraying. The state of the compound when it is brought into contact with the Ag layer 13 is also not particularly limited, and the liquid organic compound may be brought into contact as is, or the organic compound may be dissolved, dispersed, or diluted using a solvent or water as appropriate before being brought into contact. When the solution containing the organic compound is brought into contact with the Ag layer 13, the pH may be adjusted to about 5 to 7 before being brought into contact in order to improve the stability of the organic compound. In this case, it is preferable to use sulfuric acid, nitric acid, hydrochloric acid, phosphoric acid, or the like as a pH adjuster. After the contact, the organic compound that is excessive for forming the coating layer 2 of the desired thickness may be appropriately removed by washing with a solvent or water.

[0043] The organic compound forming the coating layer 2 is not particularly limited in type as long as it has a mercapto group. The number of mercapto groups contained in the molecule of the organic compound is also not particularly limited, and may be one, two (dithiol), or even three or more. The organic compound constituting the coating layer 2 may be only one type, or two or more types may be mixed.

[0044] In the R-SH structure of an organic compound, the R portion is mainly composed of C atoms and H atoms, but in addition to these atoms, it may contain heteroatoms such as N, O, S, P, and Si as appropriate. The R portion may be composed only of a chain structure, or may contain a cyclic structure at least in part. Examples of the chain structure constituting the R portion include hydrocarbon groups such as alkyl groups, alkenyl groups, and alkynyl groups, and those in which some of the C atoms constituting these hydrocarbon groups are replaced with heteroatoms. The chain structure may be a straight chain structure or may have branches. The cyclic structure constituting the R portion may be either a non-aromatic ring or an aromatic ring. Examples of the non-aromatic ring include aliphatic rings such as cycloalkyl rings, and those in which some of the C atoms are replaced with heteroatoms. Examples of the aromatic ring that does not contain a heteroatom include a benzene ring. Examples of aromatic rings containing heteroatoms, that is, heterocycles, include imidazole rings, triazine rings, isocyanuric acid skeletons, pyridine rings, pyrazine rings, pyrimidine rings, pyridazine rings, pyrazole rings, triazole rings, thiazole rings, thiophene rings, and pyrrole rings. The aromatic rings may be condensed with two or more rings. In this case, the condensed aromatic rings may be of the same kind (e.g., naphthalene rings) or may be of different kinds (e.g., benzothiazole rings and benzimidazole rings). The R portion may include both a chain structure and a cyclic structure, and the R portion may include a plurality of chain structures and / or cyclic structures. In addition, a suitable substituent may be introduced into the chain portion and / or cyclic portion, and in particular, it is preferable that a functional group capable of interacting with or forming a bond with the surface of the Ag layer 13 is introduced in addition to the mercapto group. The molecular weight of the R portion is not particularly limited, but from the viewpoint of increasing the stability of the structure in which the coating layer 2 coats the Ag layer 13, it is preferably 50 or more, and more preferably 100 or more. On the other hand, from the viewpoint of ease of forming the coating layer 2 by contact with the Ag layer 13, it is preferable that the molecular weight of the R portion is 1000 or less.

[0045] Among the various compounds listed above, it is particularly preferable that the organic compound having a mercapto group constituting the coating layer 2 has an aromatic ring. Then, the stability of the structure in which the coating layer 2 covers the surface of the Ag layer 13 is improved, and the effect of suppressing adhesion of the Ag layer 13 is enhanced. In particular, the effect of suppressing adhesion of the Ag layer 13 in a high-temperature environment is excellent. This is considered to be because the conjugated π electron system of the aromatic ring having a planar structure interacts with the surface of the Ag layer 13, and in combination with the interaction between the S atom and the Ag atom derived from the mercapto group, the coating layer 2 is firmly fixed to the surface of the Ag layer 13. Among them, when the organic compound contains a heteroaromatic ring containing at least one of an S atom and an N atom as a hetero atom in addition to a C atom, the coating layer 2 formed is particularly effective in suppressing adhesion of the Ag layer 13 and maintaining the adhesion suppression effect at high temperatures. This is presumably due to the interaction between the heteroatom contained in the ring structure and the surface of the Ag layer 13 enhancing the binding of the coating layer 2 to the Ag surface. The aromatic ring may contain only one heteroatom or may contain multiple heteroatoms, but preferably contains multiple heteroatoms.Furthermore, it is preferable that at least S atom is contained in the aromatic ring.Furthermore, when the organic compound has an aromatic ring, it is particularly preferable that the mercapto group is bonded to a position close to the aromatic ring.For example, it is preferable that the mercapto group is directly bonded to the aromatic ring, or that the mercapto group is bonded to a C atom directly bonded to the aromatic ring.

[0046] Examples of organic compounds having a mercapto group and a heteroaromatic ring that can be suitably used to form the coating layer 2 include, but are not limited to, the following. These compounds may be used alone or in combination of two or more. (2-mercaptoethyl)pyrazine, 2-mercaptobenzimidazole, 2-mercapto-5-methylbenzimidazole, 5-amino-2-mercaptobenzimidazole, 2-mercaptobenzothiazole, 6-amino-2-mercaptobenzothiazole, 2-mercapto-5-methoxybenzothiazole, 2-mercapto-6-nitrobenzothiazole, 2-mercaptopyridine, 4-mercaptopyridine, 3-pyridyl isocyanate, 3-nitropyridine-2-thiol, 2-mercapto-5-nitropyridine, thiocyanuric acid, 6 -(Dibutylamino)-1,3,5-triazine-2,4-dithiol, Tris[2-(3-mercaptopropionyloxy)ethyl]isocyanurate, 2-(Dibutylamino)-1,3,5-triazine-4,6-dithiol, 6-diallylamino-1,3,5-triazine-2,4-dithiol, 6-(4-vinylbenzyl-n-propyl)amino-1,3,5-triazine-2,4-dithiol, 6-(Diisopropylamino)-1,3,5-triazine-2,4-dithiol, 6-anilino-1,3,5-triazine-2,4-dithiol

[0047] Examples of organic compounds having a mercapto group and an aromatic ring other than a heteroaromatic ring that can be suitably used to form the coating layer 2 include, but are not limited to, the following. These compounds may be used alone or in combination of two or more. 2-phenylethanethiol, benzenethiol, benzyl mercaptan, m-toluenethiol, o-toluenethiol, p-toluenethiol, 2-aminobenzenethiol, 3-aminobenzenethiol, 4-aminobenzenethiol, 2-hydroxybenzenethiol, 3-hydroxybenzenethiol, 4-hydroxybenzenethiol, 2-phenylethanethiol, 3,4-dimethylbenzenethiol, 3,5-dimethylbenzenethiol, 4-methylbenzyl mercaptan, 2,4-dimethylbenzenethiol, 2,5-dimethylbenzenethiol, 2-methoxybenzenethiol, 3-methoxybenzenethiol, 4-Methoxybenzenethiol, 1,3-benzenedithiol, 1,4-benzenedithiol, 2-isopropylbenzenethiol, 4-isopropylbenzenethiol, 4-(dimethylamino)benzenethiol, thiosalicylic acid, 3-mercaptobenzoic acid, 4-mercaptobenzoic acid, 4-methoxy-α-toluenethiol, 3-ethoxybenzenethiol, 4-nitrobenzenethiol, 4-(methylthio)benzenethiol, toluene-3,4-dithiol, 2-naphthalenethiol, 4-tert-butylbenzenethiol, methyl mercaptobenzoate, 1,3-benzenedimethanethiol, 1,4-benzenedimethanethiol

[0048] In addition to those having an aromatic ring, examples of organic compounds having a mercapto group that can be suitably used to form the coating layer 2 include, but are not limited to, the following. These compounds may be used alone or in combination of two or more. 1-Propanethiol, Isobutyl Mercaptan, 1-Butanethiol, 2-Butanethiol, 3-Mercapto-1-Propanol, Cyclopentanethiol, 3-Mercapto-2-Butanol, 2-Methyl-1-Butanethiol, 1-Pentanethiol, Isoamyl Mercaptan, 3-Methyl-2-Butanethiol, 3-Mercapto-2-Butanol, α-Thioglycerol, 1,3-Propanedithiol, 1,2-Propanedithiol, Cyclohexanethiol, 2-Methyltetrahydrofuran-3-thiol, 3-Mercapto-2-Pentanone, Hexyl Mercaptan, 3-Mercaptoy isobutyric acid, methyl 3-mercaptopropionate, 3-mercapto-3-methyl-1-butanol, L-cysteine, 1,2-butanedithiol, 1,4-butanedithiol, 2,3-butanedithiol, 2,3-dimercapto-1-propanol, 4-mercapto-4-methyl-2-pentanone, 1-heptanethiol, 1,5-pentanedithiol, 1-(mercaptomethyl)cyclopropaneacetic acid, 1-octanethiol, 2-ethyl-1-hexanethiol, isopropyl 3-mercaptopropionate, D-penicillamine, thiomalic acid, 1,6-hexaneedithiol, dithioerythritol EXAMPLES

[0049] Examples are shown below. Note that the present invention is not limited to these examples. Here, the effect of suppressing Ag adhesion by forming a coating layer on the surface of the Ag layer was confirmed, and the difference in effect due to the hardness of the Ag layer and the type of organic compound that constitutes the coating layer was examined. Unless otherwise stated, the preparation and evaluation of samples were performed in air at room temperature.

[0050] <Sample preparation> First, a metal material was prepared. Specifically, a Ni layer having a thickness of 1 μm was formed on the surface of a clean Cu alloy substrate by electroplating. Furthermore, an Ag layer having a thickness of 5 μm was formed on the surface of the Ni layer by electroplating. Here, two types of Ag layers were prepared: a hard Ag layer and a soft Ag layer. The hard Ag layer was hardened by including 0.01 atomic % of Se relative to Ag, and had a surface hardness of 130 HV. The soft Ag layer did not include any additional element for hardening, and had a surface hardness of 60 HV.

[0051] Next, the metal material with the hard Ag layer and the metal material with the soft Ag layer prepared above were processed into flat test pieces and embossed test pieces (R=3 mm or R=20 mm), and a coating layer was formed on the surface of the Ag layer of each test piece. Specifically, each organic compound shown in Tables 1 and 2 was dissolved in water to a concentration of 150 ppm, and phosphoric acid was added to adjust the pH to 5 to prepare a raw material solution. Each test piece prepared above was immersed in the raw material solution for 30 seconds. After that, the sample surface was cleaned in a water washing process and dried to obtain a test sample. Separately, test pieces of the same shape were prepared for metal materials without a coating layer.

[0052] <Evaluation method> The adhesion resistance of each test sample obtained above was evaluated. In the evaluation, the embossed test piece was brought into contact with the surface of the flat test piece, and the Ag layer of the flat test piece and the Ag layer of the embossed test piece were brought into contact with each other at the top of the embossment via the coating layer that covers the respective surfaces. In this state, a surface pressure was applied from the embossed test piece to the flat test piece. At this time, the test pieces were replaced with each other, and two types of surface pressure, a large surface pressure and a small surface pressure, were applied. For the large surface pressure, an emboss with R=3 mm was used and a surface pressure of 220 MPa was applied, and for the small surface pressure, an emboss with R=20 mm was used and a surface pressure of 60 MPa was applied.

[0053] Each set of test pieces was left at room temperature for 2000 hours with the surface pressure applied as described above. After that, the adhesion state of the contact area between the test pieces was evaluated by energy dispersive X-ray analysis using a scanning electron microscope (SEM / EDX). When almost no adhesion traces were observed, the adhesion resistance was evaluated as very high "A+", and when adhesion traces were observed and some peeling of Ag was observed but no exposure of the underlying Ni layer was observed, the adhesion resistance was evaluated as high "A". On the other hand, when exposure of the underlying Ni layer was observed, the adhesion resistance was evaluated as low "B". Samples rated as low adhesion resistance (B) were deemed not suitable for practical use.

[0054] Furthermore, a newly prepared set of test pieces was left at a high temperature of 140°C for 500 hours with the same surface pressure applied as above. After that, the adhesion state of the contact area between the test pieces was evaluated using the same evaluation method and criteria as above to evaluate the high-temperature adhesion resistance. In addition, for the samples with a coating layer formed using some organic compounds and the samples without a coating layer, the time until adhesion occurred when a large surface pressure was applied and the underlying Ni layer was exposed was measured and recorded.

[0055] <Evaluation Results> Tables 1 and 2 below show the results of evaluation of adhesion resistance at room temperature and high temperature when large and small surface pressures were applied for samples A1 to A16 and samples B1 to B16, which have coating layers formed using various organic compounds on the surfaces of the hard Ag layer and soft Ag layer, respectively, and sample B17, which has a hard Ag layer without a coating layer.

[0056] [Table 1]

[0057] [Table 2]

[0058] According to Tables 1 and 2, first, in sample B17, which does not have a coating layer formed on the surface of the Ag layer, when a large surface pressure is applied, the Ni underlayer is exposed even at room temperature (adhesion resistance: B). In other words, even if the Ag layer is made of hard Ag, when a large surface pressure is applied and the Ag layers come into direct contact with each other, adhesion of Ag occurs. In samples B1 to B16, in which a coating layer is formed on the surface of a soft Ag layer, high adhesion resistance (A) is obtained at room temperature, at least when a small surface pressure is applied. However, regardless of which compound is used to form the coating layer, high-temperature adhesion resistance (B) is low. In other words, by providing a coating layer made of an organic compound having a mercapto group on the surface of the Ag layer, even if the Ag layer is made of soft Ag, which is relatively prone to adhesion, adhesion of Ag can be suppressed in a room temperature environment, but adhesion of Ag cannot be sufficiently suppressed in a high-temperature environment.

[0059] On the other hand, in the samples A1 to A16 in which a coating layer is formed on the surface of the hard Ag layer, very high adhesion resistance is obtained at room temperature for all samples, regardless of the surface pressure (A+). In other words, by providing a coating layer composed of an organic compound having a mercapto group on the surface of the hard Ag layer, Ag adhesion is less likely to occur than when a similar coating layer is provided on the surface of the soft Ag layer. Furthermore, the high-temperature adhesion resistance is also high in all of the samples A1 to A16 (A or A+). Compared with the samples B1 to B16 in which a coating layer is provided on the surface of the soft Ag layer, all of which had low high-temperature adhesion resistance (B), the high-temperature adhesion resistance is significantly improved. In other words, by providing a coating layer on the surface of the hard Ag layer, Ag adhesion is less likely to occur compared to when a coating layer is provided on the surface of the soft Ag layer, and Ag adhesion in a high-temperature environment is particularly effectively suppressed.

[0060] When comparing the high-temperature adhesion resistance of samples A1 to A16, which have different compound types constituting the coating layer, samples A1 to A5, which use compounds without aromatic rings, are evaluated as high (A) at all surface pressures, whereas samples A6 to A9, which use compounds with aromatic rings that are not heteroaromatic rings, are evaluated as very high (A+) at low surface pressures, and samples A10 to A16, which use compounds with heteroaromatic rings, are evaluated as very high (A+) at high surface pressures. From this, it can be seen that the effect of suppressing adhesion of the Ag layer at high temperatures is higher when forming a coating layer using organic compounds with aromatic rings, such as samples A6 to A16, than when organic compounds without aromatic rings, such as samples A1 to A5. In particular, when organic compounds with heteroaromatic rings containing heteroatoms, such as samples A10 to A16, are used, the effect of suppressing adhesion of the Ag layer at high temperatures is particularly high.

[0061] Next, Table 3 below shows the time until the Ni underlayer is exposed under high-temperature conditions under high surface pressure for cases where no coating layer is formed on the surface of the hard Ag layer and the soft Ag layer, and for cases where a coating layer made of some organic compound is formed. Each sample listed in Table 3, except for sample B18, corresponds to the sample with the same number listed in Tables 1 and 2.

[0062] [Table 3]

[0063] According to Table 3, whether the Ag layer is hard Ag or soft Ag, and whether any organic compound is used, the time until the Ni underlayer is exposed is longer when the coating layer is provided than when the coating layer is not provided. In other words, the formation of the coating layer makes it difficult for Ag to adhere. When comparing a sample with a coating layer provided on a hard Ag layer and a sample with a coating layer provided on a soft Ag layer, when the coating layer is formed using the same organic molecule, the time until the Ni underlayer is exposed is significantly longer when the coating layer is provided on the hard Ag layer, making it difficult for Ag to adhere. This also corresponds to the evaluation results of adhesion resistance shown in Tables 1 and 2 above. In addition, the time until the Ni underlayer is exposed, which is more than 1000 hours, when a coating layer is provided on the surface of the hard Ag layer is sufficiently long in consideration of the adhesion suppression effect required for connection terminals.

[0064] Furthermore, the extent to which the time until the Ni underlayer is exposed is extended by providing a coating layer is compared between the hard Ag layer and the soft Ag layer. In the case of the soft Ag layer, the formation of the coating layer extends the time until the Ni underlayer is exposed by a factor of only 10 at most, whereas in the case of the hard Ag layer, the formation of the coating layer extends the time until the Ni underlayer is exposed by a factor of more than 40. In other words, whether the Ag layer is made of soft Ag or hard Ag, the effect of providing a coating layer on the surface is able to suppress the adhesion of Ag, but it can be seen that the adhesion suppression effect of the coating layer is relatively greater in the case of the hard Ag layer. From this, as seen in the comparison of samples A1 to A16 and samples B1 to B16 in Tables 1 and 2, the phenomenon in which the adhesion resistance and high-temperature adhesion resistance of samples with a coating layer are higher when the Ag layer is hard Ag than when it is soft Ag is attributed not only to the contribution of the difference in hardness of the Ag layer itself, but also to the difference in the magnitude of the effect that the formation of the coating layer has on improving adhesion. In other words, by making the Ag layer coated on the coating layer a hard Ag layer, a very high effect can be obtained in suppressing Ag adhesion due to the high hardness of the Ag layer itself as well as the magnitude of the effect brought about by the formation of the coating layer.

[0065] Although the embodiments of the present disclosure have been described in detail above, the present invention is not limited to the above-described embodiments, and various modifications are possible without departing from the gist of the present invention. [Explanation of symbols]

[0066] 1. Materials for electrical connection components (connection materials) 10 Metal materials 11 Base material 12 Base layer 13 Ag layer 2 Covering layer 20 Female connector terminal 21 Elastic contact piece 21a Embossed section 22 Internal facing contact surface 23 Clamping section 30 Male connector terminal

Claims

1. A metal material having a Ag layer on its surface; A coating layer that coats a surface of the metal material, The material for electrical connection members, wherein the coating layer is formed by bringing an organic compound having a mercapto group and an aromatic ring into contact with the surface of the metal material. However, this does not include the case where the surface hardness of the Ag layer is 90 HV or more.

2. The material for electrical connection members according to claim 1 , wherein the aromatic ring is a heterocycle containing at least one of an S atom and an N atom in addition to a C atom.

3. 3. The material for electrical connection members according to claim 1, wherein the Ag layer has a surface hardness of 60 HV or less.

4. An electrical connection member comprising the material for electrical connection members according to any one of claims 1 to 3.

5. The electrical connection member is configured as a connection terminal having a contact portion that electrically contacts a mating conductive member, The electrical connection member according to claim 4 , wherein the coating layer is formed on a surface of the metal material at least in the contact portion.

6. 6. The electrical connection member according to claim 5, wherein the surface pressure applied to the contact portion is equal to or less than a surface pressure of 60 MPa applied to the surface of a flat test piece formed from the electrical connection member using an embossment with R = 20 mm formed from the electrical connection member.

Citation Information

Patent Citations

  • Core protecting system at trip of nuclear reactor recirculation pump

    JP1981001396A

  • Surface treatment of ag-coated cu material

    JP1985258483A

  • Foamed material for exterior use and production thereof

    JP1992002676A

  • Post-treatment of silver plating

    JP1992110474A

  • Method for improving the solderability of a surface

    JP2004510886A